Cluster randomised controlled trial to investigate the effectiveness and cost-effectiveness of a Structured Health Intervention For Truckers (the SHIFT study): a study protocol - Stacy Clemes; Veronica Varela-Mato; Fehmidah Munir; Charlotte Edwardson; Yu-Ling Chen; Mark Hamer; Laura Gray; Nishal Bhupendra Jaicim; Gerry Richardson; Vicki Johnson; Jacqui Troughton; Thomas Yates; et al. (2019)
Introduction Heavy goods vehicle (HGV) drivers exhibit higher than nationally representative rates of obesity, and obesity-related comorbidities, in comparison to other occupational groups. Their working environments are not conducive to a healthy lifestyle, yet there has been limited attention to health promotion efforts. We have developed a Structured Health Intervention For Truckers (the SHIFT programme), a multicomponent, theory-driven, health-behaviour intervention targeting physical activity, diet and sitting in HGV drivers. This paper describes the protocol of a cluster randomised controlled trial designed to evaluate the effectiveness and cost-effectiveness of the SHIFT programme.Methods and analysis HGV drivers will be recruited from a logistics company in the UK. Following baseline measurements, depots (clusters) will be randomised to either the SHIFT intervention or usual-care control arm (12 clusters in each, average cluster size 14 drivers). The 6-month SHIFT intervention includes a group-based interactive 6-hour education session, worksite champion support and equipment provision (including a Fitbit and resistance bands/balls to facilitate a ‘cab workout’). Objectively measured total daily physical activity (steps/day) will be the primary outcome. Secondary outcomes include: objectively measured light-intensity physical activity and moderate-to-vigorous physical activity, sitting time, sleep quality, markers of adiposity, blood pressure and capillary blood markers (glycated haemoglobin, low-density lipoprotein-cholesterol, high-density lipoprotein-cholesterol). Self-report questionnaires will examine fruit and vegetable intake, psychosocial and work outcomes and mental health. Quality of life and resources used (eg, general practitioner visits) will also be assessed. Measures will be collected at baseline, 6 and 12 months and analysed according to a modified intention-to-treat principle. A full process evaluation and cost-effectiveness analysis will be conducted.Ethics and dissemination Ethical approval was obtained from the Loughborough University Ethics Approvals Sub-Committee (reference: R17-P063). Study findings will be disseminated through publications in research and professional journals, through conference presentations and to relevant regional and national stakeholders via online media and at dissemination events.Trial registration number ISRCTN10483894.